2004
DOI: 10.1111/j.1467-9353.2003.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Valuing New Varieties: Trade-Offs between Growers and End-Users in Wheat

Abstract: Variety release decisions usually involve trade-offs between growers and end-users as well as substantial uncertainties about agronomic, quality, and economic variables. In this paper, methodologies were developed to value grower and end-user characteristics for individual wheat varieties and to evaluate trade-offs. The models capture effects of variability in agronomic, quality, and economic variables and were applied to experimental and hypothetical varieties. Results indicate two experimental varieties prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…Availability, and thus price, are related to the number of years since release, as more seed stock becomes available the older the variety becomes. Dahl et al (2004) concluded, ''. .…”
Section: An Economic Theory Of Wheat Variety Selectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Availability, and thus price, are related to the number of years since release, as more seed stock becomes available the older the variety becomes. Dahl et al (2004) concluded, ''. .…”
Section: An Economic Theory Of Wheat Variety Selectionmentioning
confidence: 99%
“…Following previous literature on variety selection including Barkley and Porter (1996); Dahl et al (2004);Di Falco and Chavas (2006);and Di Falco and Chavas (2008), the focus of this research is on maximizing ex ante yield across varieties, rather than maximizing profits or revenues. This approach provides information valuable for wheat producers to enhance their ability to manage production risk, and wheat breeders, who can use the results to identify yield-increasing and risk-reducing variety combinations.…”
Section: An Economic Theory Of Wheat Variety Selectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Economic analysis has also made important contributions to wheat breeding decisions and programs including the numerous studies on breeding issues in Australia (i.e. Brennan 1988, 1990, 1997) amongst others in the United States (Lambert and Wilson 2003; Dahl et al . 2004a,b).…”
Section: Background and Previous Studiesmentioning
confidence: 99%